99.5k views
0 votes
Given: F(x) = 2x - 1; G(x) = 3x + 2; H(x) = x 2 Find H(x+a) - H(x)/a

User Yeonho
by
5.7k points

1 Answer

3 votes

Answer:

Explanation:

The stumbling block for most people is what exactly do you do the what's in the brackets of something like g(x+ 4) = 2x

The answer is, whatever you see on the left side where g(x) gets modified, you put on the right side wherever you see an x.

In this question

H( x) = x ^2

So if you see anything besides x on the left, then that's what goes on the right for x.

H(x + a) - H(x)/a = (x + a)^2 - (x^2)/a

You can expand this, but I don't see a reason for doing it.

H(x + a) - H(x)/a = (x + a)^2 - (x ^2)/a = x^2 + 2a + a^2 - x^2/a which gets you nowhere.